SAT0296 Brachial-ankle index for assessing cardiovascular risk in patients with psoriatic arthritis, psoriasis alone and controls. (23rd January 2014) - Magro-Checa, C.; Rosales-Alexander, J.L.; Orgaz-Molina, J.; Salvatierra, J.; Arias-Santiago, S.; Cantero-Hinojosa, J.; Ruiz-Carrascosa, J.C.; Raya-Άlvarez, E.
Abstract : Background: Patients with psoriatic arthritis (PsA) and with moderate to severe chronic plaque psoriasis (PS) have a higher prevalence of cardiovascular (CV) risk factors and atherosclerosis. The Ankle-Brachial pressure Index (ABPI) at rest, a non-invasive and inexpensive tool for the assessment of CV risk, is the ratio of the ankle and the brachial systolic blood pressure. This indexcan be used to identify individuals who are at high CV risk. An ankle-brachial index <0.90 suggests the presence of peripheral arterial disease and a high risk of developing CV disease. Objectives: Our aim was to determine the prevalence of an abnormal ABPI in patients with psoriatic arthritis (PsA), cutaneous psoriasis alone (PS) and healthy controls and to correlate with clinical and serological parameters. Methods: This cross-sectional study included 86 consecutive patients who fulfilled the Classification Criteria for Psoriatic Arthritis (CASPAR criteria), compared to 86 patients with cutaneous PS alone and 86 age and sex matched controls. Patients with a previous CV event and diabetics were excluded. Inflammatory arthritis in PS patients was excluded by a rheumatologist in our outpatient clinic. The ABPI was measured using a Mini Dopplex with 8 MHz Vascular Probe in the arms and legs. A ratio of <0.90 was considered abnormal. Multivariate regression analysis was used to adjust for the following variables: sex, age, body mass index, classic CV risk factors, lipid profile, duration in months since diagnosis of PsA and PS, clinical patterns of the PsA and PS, treatment, activity of the disease, and inflammatory markers (p<0.05 was considered significant). Results: The mean age of all the patients was 47, 87±11, 52 (mean ± standard deviation). The ABPI in the group of PsA patients was 0, 93±0, 09, and 20 patients (23, 25%), had an abnormal index (<0, 90), four of them (4, 65%) were mildly symptomatic (ABPI <0, 80). The mean for the ABPI calculated in PS patients was 0, 93±0, 1, and 18 patients (20, 93%) were reclassified below the threshold (<0, 90), four of them <0, 80. In the group of controls, the mean was 1, 03±0, 13, with 7 patients (8, 13%) below the threshold, none of them <0, 80. Multivariate regression analysis showed that the most important prognostic factor for predicting the ABPI was the age (p<0, 05) followed by a sedentary lifestyle (p<0, 05). Clinical patterns of the PsA and Psoriasis, treatment and activity of the disease were not associated with atherosclerosis. Conclusions: There is an increased prevalence of an abnormal ABPI in patients with PsA and PS comparing with controls implying an increased risk of cardiovascular disease. The ABPI may be a simple non-invasive tool for the early detection of accelerated atheroma in these patients. References: Alkaabi JK et al. Rheumatoid arthritis and macrovascular disease. Rheumatology (Oxford). 2003;42:292–297. Disclosure of Interest: None Declared